Physical fitness related to the health of 7–10 year-old students - Montoro, Ana Paula Pietro Nobre; Leite, Carina Raffes; Espíndola, Janine Aryadine; Alexandre, Juliano Maestri; Reis, Monalisa da Silva; Capistrano, Renata; Lisboa, Tailine; Beltrame, Thais Silva (ABCS Health Sciences, 2016)
Introduction: The physical fitness related to health refers to the physical and physiological characteristics that define the morbidity and mortality profiles. Objective: To a Assess the physical fitness related to health of 7–10 year-old students. Methods: The study included 93 7–10 year-old students of both sexes. The instrument used was the battery of tests and measures of Projeto Esporte Brasil (PROESP-BR), including (flexibility test, muscular endurance, cardiorespiratory endurance and body mass index (BMI), ”weight/height2”. Results: It was observed that the students presented desired levels of physical fitness in the tests (flexibility and BMI), but in muscular endurance and cardiopulmonary tests, they got unwanted levels considering health risk. Conclusion: Our results do not show satisfactory levels of physical fitness related to health in muscular and cardiorespiratory endurance, revealing a risk of developing non transmissible chronic diseases to students.